Experimental study on a novel thermal storage refrigerant-heated radiator coupled with air source heat pump heating system. (15th October 2019) - Zhang, Huan; Jiang, Lingfei; Zheng, Wandong; You, Shijun; Jiang, Tingting; Shao, Suola; Zhu, Xingming
Abstract: Air source heat pump (ASHP) is a sustainable and efficient technology for space heating, which has been widely used over the recent decades. In order to improve the thermal efficiency of ASHP heating system, a novel thermal storage refrigerant-heated radiator coupled with ASHP heating system is proposed. In this system, the high temperature refrigerant steam discharged from the compressor is sent to the radiator directly to heat the space through radiation and natural convection. Energy storage water is injected to the radiator to supply energy during defrosting process. A set of experiments have been conducted in a climate chamber to study the performance of the radiator and system. The results show that the radiator has less heat dissipation and uniform surface temperature. As for system performances, the coefficient of performance varies from 4.4 to 3.3 as the condensing temperature increases from 35.9 °C to 44.0 °C, and it varies from 4.2 to 1.8 as the outdoor air temperature decreases from 6.9 °C to −18.4 °C. The defrosting performance is also investigated, proving that the energy storage material can maintain a comfortable indoor air temperature during the defrosting process. Furthermore, a characteristic equation specific to the refrigerant-heated radiator is given to provide reference for future application. Highlights: A thermal storage refrigerant-heated radiator coupled with heat pump is developed. The radiator has less heat dissipation and uniform surface temperature. The coefficient of performance varies from 1.8 to 4.4 under testing conditions. Energy storage water provides 95.1% of energy during defrosting process. A characteristic equation correlating the radiator and heat pump unit is given.